Bibliometric analysis at the National Technical University Athens - Iliakis, Alexandros; Anastasopoulou, Christina (Qualitative and Quantitative Methods in Libraries; Vol 7 No 2 (2018): June 2018 Issue, 2019)
Within the framework of the internal evaluation of the National Technical University of Athens, as specified by the standards of the Hellenic Quality Assurance and Certification Authority in Higher Education, the members of the Library of the National Technical University of Athens were asked to provide information on the publishing activity of the members of its Academic Staff. After consulting with the Management and the Quality Assurance Unit of the National Technical University of Athens, it was agreed to implement a bibliometric analysis of the publications - mainly in international scientific journals - of its academic staff. In particular, it was suggested to use scientific publications - up to and including 2016 - for each active member of the academic staff. The information that had to be collected was the following: the number of publications, the number of references and the h-index.